Предмет: Математика,
автор: nyanzzu
y = 3x+2/2x+3 - Найти производную функции.
Ответы
Автор ответа:
0
y'= [(3X+2)' х(2X+3) -(3X+2)x (2X+3)']/ (2X+3)^2
y'=[3(2X+3) - (3X-2) x 2]/(2X+3)^2
y'= (6X+9 - 6X+4)/ (2X+3)^2
y'= 13/(2X+3)^2
y'=[3(2X+3) - (3X-2) x 2]/(2X+3)^2
y'= (6X+9 - 6X+4)/ (2X+3)^2
y'= 13/(2X+3)^2
Похожие вопросы
Предмет: Информатика,
автор: hjkmahe123456789
Предмет: Химия,
автор: voronasony845
Предмет: Информатика,
автор: hdjhd42
Предмет: История,
автор: 1999Alex
Предмет: Физика,
автор: нафочка14